Introduction to tools and technologies for concurrent product development - Boejang, Hambali (Penerbit UTeM Press, 2021)
This book is about the modern tools and technologies that are adopted during the concurrent product development process. These tools and technologies significantly help product developers to achieve their product development project goals in terms of development time and cost, product quality, and customer satisfaction. The tools and technologies include, for example, computer-aided design and design analysis software, reverse engineering, additive manufacturing, and rapid tooling as well as high-speed machining.